2023
DOI: 10.1186/s12882-023-03206-1
|View full text |Cite
|
Sign up to set email alerts
|

Monthly mini-dose rituximab for primary anti-PLA2R-positive membranous nephropathy: a personalized approach

Abstract: Background The currently recommended dose of rituximab for primary membranous nephropathy is as high as that for lymphoma. However, the clinical manifestations of membranous nephropathy vary widely. Therefore, achieving individualized treatment is a topic that needs to be explored. This study assessed the efficacy of monthly mini-dose rituximab monotherapy in patients with primary membranous nephropathy. Methods This retrospective study included 32… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The decision to use rituximab as the treatment modality was based on the elevated levels of anti-PLA2R, indicating a possible autoimmune component in primary membranous glomerulonephritis [18]. Rituximab, a monoclonal antibody that targets CD20-positive B cells, has shown promising results in the treatment of autoimmune glomerulonephritis [19].…”
Section: Discussionmentioning
confidence: 99%
“…The decision to use rituximab as the treatment modality was based on the elevated levels of anti-PLA2R, indicating a possible autoimmune component in primary membranous glomerulonephritis [18]. Rituximab, a monoclonal antibody that targets CD20-positive B cells, has shown promising results in the treatment of autoimmune glomerulonephritis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is more effective to maintain the residual rituximab level for a longer time than to have high peak concentration. A retrospective study was carried out by our group and revealed that monthly mini-dose (100 mg) has better short-term (6 months) clinical efficacy compared to the standard dose regimens while the cumulative dose and the rate of adverse event is much lower ( Wang et al, 2023 ). Inspired by the promising preliminary results, further studies are urgently warranted to compare with standard dosage and better optimize the dosage.…”
Section: Introductionmentioning
confidence: 99%